Emak-Emak and Srikandi Shari'ah Economic Movement Pemilu period in Indonesia - Heri Junaidi; Rusmiatiningsih Rusmiatiningsih; Chici Rima Putri Pratama (UIN Sunan Gunung Djati, 2023)
The realm of domestication of women still continues to leave studies through the study of gender studies in perspective. in line with this, sharia economics is still not present in the study of implementative studies, especially related to the economic activities of Muslim women. The presence of elections as part of this is in line with efforts to improve equality and justice between men and women in the public sphere. This study emphasizes their economic activities in the midst of Indonesia's political events that have escaped from various previous studies. This research uses a descriptive qualitative approach with data sources from various conversations in online media and relevant literature. The results show that women who are active in Islamic economics in the 2019 elections by calling the emak emak group and the Srikandi group and continue with these terms in the 2024 elections rely on the concept of maslhahah as a form of responsive participation for the success of the struggle in the public sphere as well as to help their respective family economies. This paper concludes that the economic activities of emak emak and Srikandi by building on Islamic values make an important contribution to increasing the number of women's votes included in the list of legislative candidates in Indonesia.